Plane-constraint-based calibration method for a galvanometric laser scanner. (May 2018) - Mao, Yang; Zeng, Liangcai; Jiang, Jun; Yu, Chengyi
Laser stripe vision sensors have limited application when the whole surface of an object has to be measured; therefore, a galvanometric laser scanner is presented using a one-mirror galvanometer element as its mechanical device to drive the light stripe to sweep along the object. A flexible plane-constraint together with a look-up table calibration algorithm by viewing a planar calibration target from unknown orientations is presented to calibrate the proposed galvanometric laser scanner. The plane-constraint method generates a larger number of control points by imposing a plane constraint on the control points. Compared with the invariance of double cross-ratio, the plane-constraint-based calibration method generates the same number of control points without error propagation. Contrast experiments are conducted to verify the efficiency and accuracy of the proposed calibration method.